Emergency Treatment of Acute Decompensated Severe Aortic Stenosis with Transcatheter Aortic Valve Implantation under the Coplane View Using J-Tipped Wires Fluoroscopy - Xian Liu; Yingdong Wang; Yuhe Sheng; Bin Wang; Kai Xu (Cardiology Discovery)
Patients experiencing severe aortic stenosis with acute decompensation often face elevated surgical aortic valve replacement risks, leading to high postoperative mortality rates. However, for some patients eligible for transcatheter aortic valve implantation (TAVI), computed tomography angiography for assessing the aortic root and coronary artery might be challenging before the TAVI procedure. This case highlights a patient who underwent emergency TAVI guided by coplane view generated using J-tipped wires fluoroscopy without computed tomography evaluation before the TAVI. This approach reduces contrast usage during the TAVI procedure, significantly mitigating the risks of renal injury and heart function deterioration.